Didactical Framework for the Simulation of Computer Performance Analysis - La Red Martinez, David L.; Romero, Carlos A.; Rambo, Alice R. (European Scientific Journal, ESJ, 2017)
In this paper, we discussed the main aspects of the various development carried out on the subject of "Operating systems" and "Evaluation systems of data processing" for the degree course in information systems of the FaCENA from the UNNE. Here, emphasis was placed on various algorithms for the analysis of performance in calculation systems. The motivation for the realization of this work is based on the fact that students often encounter difficulties in identifying the formula that should be used in each of the statements of the practical exercises during performance analysis. The proposal aims to provide students with a tool to complement the developed in class. It was a web application designed to encourage the process of teaching - learning, based on an applet that acts as a container in using different interfaces. Each one of them represents the execution of a method of evaluation of performance, including the law of Amdhal, performance, improvement, comparative analysis, operational analysis, workload characterization, and capacity planning. In addition, a web application that allows the self-assessment of student in achieving learning outcomes was developed. The implementation of web application, however, makes use of the b-learning, model of teaching and learning combined, that collects the advantages of the model to distance. It also takes advantage of the importance of the group, the rhythm of learning, and the direct contact with the Professor.